Antimicrobial Profile and Prevalence of Salmonella Species from Blood Culture in A Tertiary Care Hospital - Jain, Charu; Nikita (Jurnal Ilmu Kesehatan dan Kesehatan, 2023)
Background & Aim: Enteric fever is a major public health concern around the world and endemic in low- and middle-income countries like, India. Typically, it spreads through contaminated food or water. Salmonella Typhi proliferate and spread throughout the bloodstream seeding multiple organs in the body. Incidence data of culture confirmed Typhoid cases is approximately 377per 100000 population with an approximate case fatality rate of 1% in India. The management of cases are hampered due to emerging the drug resistance of isolates because of rampant and misuse of antibiotics. This study investigates to analyse the current pattern of antibiotic susceptibility among Salmonella isolates from cases of enteric fever seen at ESIC Medical College & Hospital, Faridabad. Material & Methods: This is a retrospective, cross-sectional study. Blood cultures from patients with suspected enteric fever from Jan 2017 to Dec 2019 were included. The blood cultures were processed using the BacT/Alert automated blood culture system. Results: During the study period, a total of 4064 blood culture specimens were received from the patients suspected for fever. Out of a total of 2717 culture positive samples, 373 (13.73%) were found positive for the growth of Salmonella enterica [Salmonella typhi 87.13% (325/373), Salmonella paratyphi A (12.86%)], confirming the enteric fever. Conclusion: Treatment with appropriate antimicrobial drugs is crucial for patients with typhoidal infections and the antimicrobial susceptibility of such isolates must be reported as soon as possible.